Leber’s hereditary optic neuropathy: clinical and genetic analysis of Bulgarian patients - Sylvia Cherninkova; Boryana Zaharova; Kunka Kamenarova; Kalina Mihova; Slavena Atemin; Tihomir Todorov; Vasil Haykin; Alexander Oscar; Ivailo Tournev; Radka Kaneva; Albena Todorova (Biotechnology & Biotechnological Equipment, 2023)
Leber’s hereditary optic neuropathy (LHON) is a rare maternally inherited disease caused by mutations in mitochondrial DNA (mtDNA) genes encoding subunits of complex I in the mitochondrial respiratory chain. The most common mutations causing LHON are G11778A, G3460A and T14484C, but there are also several less common mutations. LHON presents as acute or subacute bilateral visual loss, usually affecting young males. The aim of this study was to assess the clinical symptomatology and genetic analysis of Bulgarian patients with LHON. Twenty-two patients were diagnosed with LHON based on clinical evaluation and genetic examination (17 males and 5 females); 12 of them were previously reported, while 8 males and 2 females are newly diagnosed. A full neuroophthalmologic and genetic examination was performed. Eight patients had a family history of LHON, while 14 were isolated cases. The age at onset ranged from 3 to 43 years, and visual acuity ranged from counting fingers to 0.9. Genetic testing revealed various mutations, including a rare mutation G3635A in MT-ND1 in five affected members of one pedigree and digenic inheritance of G11778A and T14484C in three individuals from a different family. A variant m.15988A > G in the mitochondrial gene MT-TP with a high level of heteroplasmy was found in one patient. In addition to the most common mutations causing LHON, our patients also had rare mutations. These results suggest that genetic analysis of the entire mtDNA sequence is recommended in cases with strong clinical suspicion of LHON, since new rare mtDNA pathogenic variants are being identified.